Oligomerization of the UapA purine transporter is critical for ER-exit, plasma membrane localization and turnover. - Martzoukou, Olga; Karachaliou, Mayia; Yalelis, Vassilis; Leung, James; Byrne, Bernadette; Amillis, Sotiris; Diallinas, George (J Mol Biol, 2015)
Central to the process of transmembrane cargo trafficking is the successful folding and exit from the ER through packaging in COPII vesicles. Here, we use the UapA purine transporter of Aspergillus nidulans to investigate the role of cargo oligomerization in membrane trafficking. We show that UapA oligomerizes (at least dimerizes) and that oligomerization persists upon UapA endocytosis and vacuolar sorting. Using a validated BiFC assay, we provide evidence that a UapA oligomerization is associated with ER exit and turnover, as ER-retained mutants, either due to modification of a Tyr-based N-terminal motif or partial misfolding, physically associate, but do not associate properly. Co-expression of ER-retained mutants with wild-type UapA leads to in trans plasma membrane localization of the former, confirming that oligomerization initiates in the ER. Genetic suppression of an N-terminal mutation in the Tyr motif and mutational analysis suggest that transmembrane α-helix 7 affects the oligomerization interface. Our results reveal that transporter oligomerization is essential for membrane trafficking and turnover and is a common theme in fungi and mammalian cells.